R-curve evaluation of 3YTZP/graphene composites by indirect compliance method. Issue 8 (July 2023) - López-Pernía, C.; Muñoz-Ferreiro, C.; Prada-Rodrigo, J.; Moreno, P.; Reveron, H.; Chevalier, J.; Morales-Rodríguez, A.; Poyato, R.; Gallardo-López, Á.
Abstract: This work addresses the crack growth resistance of 3 mol% Yttria-doped Tetragonal Zirconia Polycrystalline (3YTZP) spark-plasma sintered (SPS) composites containing two types of graphene-based nanomaterials (GBN): exfoliated graphene nanoplatelets (e-GNP) and reduced graphene oxide (rGO). The crack growth resistance of the composites is assessed by means of their R-Curve behavior determined by three-point bending tests on single edge "V" notched beams (SEVNB), in two different orientations of the samples: with the crack path perpendicular or parallel to the pressure axis during the SPS sintering. The sharp edge notches were machined by ultrashort laser pulsed ablation (UPLA). The compliance and optical-based methods for evaluating the crack length are compared on the basis of the experimental R-Curve results in composites with 2.5 vol% rGO tested in the perpendicular orientation. Moreover, the activation of reinforcement mechanisms is evaluated by both the fracture surface inspection by Scanning Electron Microscopy and a compliance analysis. It is shown that the indirect compliance method is relevant and reliable for calculating the R-Curve of 3YTZP/GBN composites. The effect of the type and content of GBN on the crack growth resistance of the composites is also discussed. Highlights: Simple and accurate measurement of the R-Curve of GBN/3YTZP composites. GBN aspect ratio and orientation determine composite crack propagation resistance. Noteworthy different crack growth resistance of e-GNP and rGO composites. No significant reinforcement by the incorporation of e-GNP into the ceramic matrix. Large rGO perpendicular to the crack path remarkably reinforces the composite.